2006
DOI: 10.1002/ps.1178
|View full text |Cite
|
Sign up to set email alerts
|

Farmer perceptions and pesticide use practices in vegetable production in Ghana

Abstract: As an initial part of a programme aimed at promoting safe and sound agricultural practices in Ghana, a study was made of farmers' perceptions of pesticides for use and application in vegetable production, using a small survey of 137 farmers who applied pesticides. Field surveys, interviews, questionnaires and analytical games were used to obtain information on the type, scope and extent of use of pesticides, farmers' knowledge of pesticides, and their perceptions about the chemicals' potential for harm. Data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
291
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 312 publications
(326 citation statements)
references
References 9 publications
(11 reference statements)
30
291
2
3
Order By: Relevance
“…Empirically, specific studies have shown the high human and environmental risks of unsafe use of pesticides in many African countries such as Ghana (Ntow et al 2006), Tanzania (Ngowi et al 2007), Botswana (Obopile et al 2008), Ethiopia (Jansen and Harmsen 2011), Benin (Ahouangninou et al 2012), Uganda (Kateregga 2012), Kenya (Macharia et al 2013). Other parts of sub-Saharan Africa have similar problems with the widespread use of highly toxic and illegal pesticides (Ecobichon 2001;Williamson et al 2008;Handford et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, specific studies have shown the high human and environmental risks of unsafe use of pesticides in many African countries such as Ghana (Ntow et al 2006), Tanzania (Ngowi et al 2007), Botswana (Obopile et al 2008), Ethiopia (Jansen and Harmsen 2011), Benin (Ahouangninou et al 2012), Uganda (Kateregga 2012), Kenya (Macharia et al 2013). Other parts of sub-Saharan Africa have similar problems with the widespread use of highly toxic and illegal pesticides (Ecobichon 2001;Williamson et al 2008;Handford et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These practices are not governed by strict regulations concerning the training and education of farmers. As information from the questionnaire and previous work (Clarke et al 1997;Ntow et al 2006) revealed that farmers' handling and storage of chemical pesticides, personal hygiene, and the proper use of personal protective equipment in Ghana is below a reasonable standard, it is unexpected that the biological exposure marker failed to demonstrate an equivalent result.…”
Section: Discussionmentioning
confidence: 99%
“…Akumadan lies in the agricultural zone of the Ashanti Region of Ghana. The community at Akumadan is noted for the cultivation of (Ntow et al 2006). On the one hand, most farmers at Akumadan have little (64.9% comprising primary and middle) or no formal education (12.7%) (Ntow et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations